Targeting BAM for Novel Therapeutics against Pathogenic Gram-Negative Bacteria - Claire Overly Cottom; Robert Stephenson; Lindsey Wilson; Nicholas Noinaj (Antibiotics, 2023)
The growing emergence of multidrug resistance in bacterial pathogens is an immediate threat to human health worldwide. Unfortunately, there has not been a matching increase in the discovery of new antibiotics to combat this alarming trend. Novel contemporary approaches aimed at antibiotic discovery against Gram-negative bacterial pathogens have expanded focus to also include essential surface-exposed receptors and protein complexes, which have classically been targeted for vaccine development. One surface-exposed protein complex that has gained recent attention is the β-barrel assembly machinery (BAM), which is conserved and essential across all Gram-negative bacteria. BAM is responsible for the biogenesis of β-barrel outer membrane proteins (β-OMPs) into the outer membrane. These β-OMPs serve essential roles for the cell including nutrient uptake, signaling, and adhesion, but can also serve as virulence factors mediating pathogenesis. The mechanism for how BAM mediates β-OMP biogenesis is known to be dynamic and complex, offering multiple modes for inhibition by small molecules and targeting by larger biologics. In this review, we introduce BAM and establish why it is a promising and exciting new therapeutic target and present recent studies reporting novel compounds and vaccines targeting BAM across various bacteria. These reports have fueled ongoing and future research on BAM and have boosted interest in BAM for its therapeutic promise in combatting multidrug resistance in Gram-negative bacterial pathogens.